Islamic mysticism : a short history. - Knysh, Alexander. (Themes in Islamic Studies, 2015)
The book provides a general survey of the history of Islamic mysticism (Sufism) since its inception up to the modern time. It combines chronological and personality-based approaches to the subject with a thematic discussion of principal Sufi notions and institutions. Sufism is examined from a variety of different perspectives: as a vibrant social institution, a specific form of artistic expression (mainly poetic), an ascetic and contemplative practice, and a distinctive intellectual tradition that derived its vitality from a dialogue with other strands of Islamic thought. The book emphasizes the wide variety of Sufism's interactions with the society and its institutions from an ascetic withdrawal from the world to an active involvement in its affairs by individual Sufi masters and organizations. Islamic Mysticism by Knysh is a comprehensive survey of the interesting and fascinating world of Islamic Mysticism.